Penataan Prasarana Kawasan Permukiman Tepian Kanal Jongaya Berbasis Masyarakat - Mimi Arifin; A. Yudhono; S. Trisutomo; S. Wunas; Y. Jinca; Arifuddin Akil; A.R. Rasyid; I. Latief; M. Ali; F. Azmy; Y.K. Dewi; W.W. Osman; S.A. Ekawati; S. Wahyuni; L.M. Asfan; G. Lakatupa (Faculty of Engineering UNHAS, 2019)
The residential area which is on the outskirts of the Jongaya Canal as one of the causes of pollution of the abiotic environment such as high quality garbage accumulation which has an impact on the pollution of Losari Beach as one of the landmarks of Makassar City. The Bontorannu urban area has several potentials that can be used as a supporting factor to encourage the revitalization of channels that can be used as air transportation because the Jongaya canal can be connected to Losari Beach and the surrounding islands, Coastal corridor fishing settlements (Makassar City RTRW 2015-2034) have a value more as an Integrated Business and Tourism Center. The purpose of community service is to 1) Identify the characteristics of the infrastructure of community settlements and the community's preference for the edge settlement of the Jongaya Canal in the Bontorannu Village, Mariso District, Makassar City. 2) Arranging directives in the slums in the Bontorannu Village, Mariso District, Makassar City, based on the community. The method used is appropriate stimulus assistance for the community because the required stimulus is engineered so that people's perceptions of the environment and settlements are as expected. The socialization on structuring the settlement area infrastructure has been carried out and approved by the people of the banks of the Jongaya canal directly, and has received feedback from the participants about the suggestions and assistance on how to improve community-based settlement infrastructure